2004
DOI: 10.1007/s00464-003-9259-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colorectal surgery in obese and nonobese patients: Do differences in body mass indices lead to different outcomes?

Abstract: These data indicate that laparoscopic colorectal surgery is feasible and effective in both obese and nonobese patients. Obese patients who are thought to be at increased risk of postoperative morbidity have the similar benefit of laparoscopic surgery as nonobese patients with colorectal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 18 publications
3
94
3
3
Order By: Relevance
“…Severely morbid patients are believed to have even more comorbidities, as these conditions are more prevalent as the BMI increases (1). Some recent studies have demonstrated that it doesn't necessarily correlate with more postoperative comorbidities (15)(16)(17), while a recent review described more pulmonary events, ileus and wound infection in obese cohorts than non-obese cohorts (18) The post-operative morbidity rate in our series is high, but seems equivalent to the rates described in obese patients. The anastomotic leak rate seemed comparable to the rates seen in non-morbidly obese patients and even lower than the rates described for obese patients in some series.…”
Section: Discussionmentioning
confidence: 47%
“…Severely morbid patients are believed to have even more comorbidities, as these conditions are more prevalent as the BMI increases (1). Some recent studies have demonstrated that it doesn't necessarily correlate with more postoperative comorbidities (15)(16)(17), while a recent review described more pulmonary events, ileus and wound infection in obese cohorts than non-obese cohorts (18) The post-operative morbidity rate in our series is high, but seems equivalent to the rates described in obese patients. The anastomotic leak rate seemed comparable to the rates seen in non-morbidly obese patients and even lower than the rates described for obese patients in some series.…”
Section: Discussionmentioning
confidence: 47%
“…Some reports have demonstrated that obesity is associated with high conversion rates [16][17][18]. One of the difficulties of performing laparoscopic surgery on obese patients is obtaining good visualization of the surgical field.…”
Section: Discussionmentioning
confidence: 99%
“…Although we had not specifically considered this factor, performing colectomy by minilaparotomy approach on transverse colon cancer did not pose any technical difficulties compared with that for tumors at other locations. 15 Many reports [16][17][18] described that the conversion rate was reported to be relatively high in laparoscopic-assisted colectomy because of high BMI, although several researchers 19,20 claimed that obesity did not have an adverse impact on the technical difficulties in laparoscopic techniques. Except for the tumors of midsigmoid and midtranverse colon, we have also limited the selection of patients to nonoverweight persons (BMI , 25.0 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%